2008
DOI: 10.1007/s10661-008-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular particulate matter emissions in road tunnels in Sao Paulo, Brazil

Abstract: In the metropolitan area of São Paulo, Brazil, ozone and particulate matter (PM) are the air pollutants that pose the greatest threat to air quality, since the PM and the ozone precursors (nitrogen oxides and volatile organic compounds) are the main source of air pollution from vehicular emissions. Vehicular emissions can be measured inside road tunnels, and those measurements can provide information about emission factors of in-use vehicles. Emission factors are used to estimate vehicular emissions and are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1
16

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 34 publications
7
48
1
16
Order By: Relevance
“…In the JQ tunnel, the most abundant trace elements were Fe, S, Si, Cu and Ca. With the exception of Cu, such results are in good agreement with gasohol-and ethanol-fuelled vehicles measurements in dynamometers (Ferreira da Silva et al, 2010) and in previous tunnel studies (Sánchez-Ccoyllo et al, 2009). The high abundance of Cu, linked to break lining, is attributed to a stop-go driving pattern in the JQ tunnel due to traffic congestions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the JQ tunnel, the most abundant trace elements were Fe, S, Si, Cu and Ca. With the exception of Cu, such results are in good agreement with gasohol-and ethanol-fuelled vehicles measurements in dynamometers (Ferreira da Silva et al, 2010) and in previous tunnel studies (Sánchez-Ccoyllo et al, 2009). The high abundance of Cu, linked to break lining, is attributed to a stop-go driving pattern in the JQ tunnel due to traffic congestions.…”
Section: Discussionsupporting
confidence: 89%
“…Here, the ratio for the JQ tunnel is considerably higher (8.2). It has been previously suggested that ethanol processing of copper tanks enhances gasohol-fuelled vehicles Cu emission factors (Castanho and Artaxo, 2001;Sánchez-Ccoyllo et al, 2009), thus indicating that higher Cu : Sb ratios than expected are only due to brake lining. Whether such difference is due to the suggested ethanol usage (and therefore could be used as a marker) or is due to a different brake lining composition cannot be determined from this study and demands further investigation.…”
Section: Oc Ec and Trace Elementsmentioning
confidence: 89%
“…The modeling approach taken in different cities in the southeastern region of Brazil has been evolving, and most of the efforts have been focused on the construction of a comprehensive emissions inventory. In the MASP, the emissions inventory is based on vehicle emission factors (dynamometer measurements) and tunnel measurements performed in the city of São Paulo in 2001and 2004Sánchez-Ccoyllo et al, 2009), as well as on experiments conducted in 2011 Pérez-martínez et al, 2014).…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
“…During the summer of 2013/2014 as a whole, there were 27 days on which the relative humidity was below 40%. The quality of the simulation, in comparison with direct measurement, was evaluated with the statistical parameters correlation, bias, root mean square decomposed into two components: Albuquerque et al, 2012) Emission factors for regulated pollutants and hydrocarbons 1 h Measurements inside road traffic tunnels Sánchez-Ccoyllo et al, 2009;Brito et al, 2013;Nogueira et al, 2014;Pérez-martínez et al, 2014) USP, University of São Paulo. systematic RMSDs and unsystematic RMSDu, and agreement index, according to Willmott et al (1985) and Lu et al (1997).…”
Section: Case Study: Summer 2013/2014mentioning
confidence: 99%
“…This result indicates that the fraction of fine particles represents a significant portion of PM 10 mass in both sites, similar to other urban centers and areas practicing biomass burning. [45][46][47][48] In addition, fine and ultrafine particles have diesel exhaust as a significant source in urban area, and these are the ones with the highest potential to cause cardio-respiratory diseases. 49,50 In order to examine the behavior of the atmospheric particulate matter, mass size distributions ( Figure 1) and mass concentrations of PM 10 and PM 2.5 were related with the set of meteorological data, which are presented in Table 2.…”
Section: Particulate Matter Concentrationsmentioning
confidence: 99%